Foundation of another temple with a Shiva Linga and a pillar - Temples of India Project Team (Jio Institute, 2024)
The surviving foundation of the subsidiary shrine features a flight of steps leading to the Shiva Linga placed at the center. Adjacent to the steps lies a pillar fragment, resembling those found at the southern entrance of the temple premises and at the beginning of the stairs leading to the Mahakal Temple’s mandapa. The pillar has a depiction of a standing human figure. The base of the temple has vegetal outgrowth.